The 2023 Dengue Outbreak in Bangladesh: An Epidemiological Update - Mohabbat Hossain; Md Shafiqul Islam Rakib; Md Mahedi Hasan; Shams Nur Powshi; Enayetul Islam; Nazneen Naher Islam (Health Science Reports)
ABSTRACT Background and Aims Dengue fever, a mosquito‐borne illness, has emerged as a serious hazard to public health, particularly in tropical and subtropical countries, including Bangladesh. This study aimed to depict an overall scenario of the prevalence of dengue cases and the mortality rate of dengue outbreaks in Bangladesh in 2023. Methods From January 1, 2023 to December 31, 2023, day‐to‐day data regarding dengue cases and mortality were collected and compiled from two national databases: the Directorate General of Health Services (DGHS), Ministry of Health and Family Welfare, Bangladesh, and the Institute of Epidemiology, Disease Control, and Research (IEDCR), Bangladesh. Statistical analysis was performed on Microsoft Excel 2021. Results Between January 1, 2023 and December 31, 2023, a record number of 321,179 dengue‐infected cases and 1705 deaths (0.53% of total cases) were reported since the very first dengue outbreak in Bangladesh. Males were more infected (n = 192,610, 59.97%), although females had a higher mortality rate (n = 970, 56.89%) compared to males (n = 735, 43.11%). The highest rates of infection (n = 145,571, 45.32%) and death (n = 593, 34.78%) were seen among those under the age group of > 20–40 years. With 79,598 cases (24% of total cases) and 396 deaths (23.23% of all deaths), the month of September recorded the highest peak of the dengue outbreak. Furthermore, Dhaka recorded half of all infected cases (n = 169,321, 52.72%) and the majority (n = 1163, 68.21%) of dengue deaths, according to the division‐wise distribution of cases and deaths. Conclusion The findings of the study will be helpful in understanding the dengue situation in Bangladesh and will contribute to further investigations on dengue outbreaks targeting the progression and importance of identifying the circulating DENV serotypes.